The Contributions of Teacher Humor in EFL Classes in Vietnam: University Students’ Perspectives - Pham Trut Thuy; Le Thanh Thao (Vision: Journal for Language and Foreign Language Learning, 2022)
According to several studies on English teaching and learning, English as a foreign language (EFL) teachers tend to avoid humor in their classrooms. However, many studies have shown that teachers’ sense of humor plays an essential role in EFL students’ learning process. Therefore, this study utilizing a mixed-method design was conducted to determine students’ perceptions of the impact of teachers’ humor (TH) on their learning. Data were collected through a questionnaire with a five-point Likert scale comprising twenty-one items and semi-structured interviews. The study involved 158 university students in the Mekong Delta of Vietnam. Quantitative data from the questionnaire were analyzed by using SPSS 20.0, and data from the interviews were analyzed according to themes. The survey results revealed that the students showed positive attitudes toward the effects of TH in EFL classrooms, especially reducing boredom (M=4.59), strengthening teacher-student rapport (M=4.53), decreasing sleepiness (M=4.47), promoting students’ cheerfulness (M=4.47), increasing students’ consciousness (M=4.46), and solving conflicts in classrooms (M=4.42). Additionally, non-majored students were appreciated for TH more than their counterparts. Moreover, students’ perceptions positively correlated with their gender. The interviews also showed that cultural factors affected the effectiveness of TH in EFL classes. EFL teachers are encouraged to use TH in their classes in order to foster its benefits. However, careful consideration should be taken before using TH in teaching different students with different learning styles or characteristics.